Surgical odyssey in treating recurrent congenital nasal pyriform aperture stenosis - Md Ali, Saidatur Rabiqah Adawiyah; Mohd Nor, Khadijah; Abu Bakar, Saraiza; Sheikh Ab Hamid, Suzina (Springer, 2024)
We present a case report of congenital nasal pyriform aperture stenosis, in which the child was managed with a series of less invasive surgical procedures, which were eventually followed by repair via a sublabial approach. This case report aims to highlight that in severe stenosis, earlier open surgical intervention with bone drilling is suggested, as dilatation alone will result in recurrent stenosis. Open surgery with bone drilling not only facilitates faster recovery but also aids in oxygen weaning, shortens hospitalization duration, and reduces the risk of complications.